2019
DOI: 10.1093/cdn/nzz031.p06-042-19
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Impact of Xanthorrhizol and d-δ-tocotrienol on the Proliferation of Murine B16 Melanoma Cells and Human DU145 Prostate Carcinoma Cells (P06-042-19)

Abstract: Objectives Xanthorrhizol, a sesquiterpene, and d-δ-tocotrienol, a vitamin E molecule, each suppresses the proliferation of a number of tumor cells. This study aims to examine the potentially synergistic effect of xanthorrhizol and d-δ-tocotrienol in tumor cells. Methods Murine B16 melanoma and human DU145 prostate carcinoma cells were incubated for 48 h (B16) or 72 h (DU145) with xanthorrhizol or d-δ-tocotrienol before cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, it also showed the ability as an antiproliferative and inhibitor when tested on human hepatoma and breast cancer cells 5,6,41 . A recent study documented the tumor suppressive role of XNT on the prostrate carcinoma cells which revealed that XNT exerts its antiproliferatory impact by inducing G1 cycle arrest 42 . However, the precise mechanism of influence on cell cycle regulation of XNT and underlying molecular targets still remain to be discovered.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it also showed the ability as an antiproliferative and inhibitor when tested on human hepatoma and breast cancer cells 5,6,41 . A recent study documented the tumor suppressive role of XNT on the prostrate carcinoma cells which revealed that XNT exerts its antiproliferatory impact by inducing G1 cycle arrest 42 . However, the precise mechanism of influence on cell cycle regulation of XNT and underlying molecular targets still remain to be discovered.…”
Section: Resultsmentioning
confidence: 99%